Using ESI FT-ICR MS to Characterize Dissolved Organic Matter in Salt Lakes with Different Salinity - Xu, Wei; Gao, Qiang; He, Chen; Shi, Quan; Hou, Zheng-Qing; Zhao, Hua-Zhang (Environmental science & technology, 2020)
Dissolved organic matter (DOM) composition in salt lakes is critical for water quality and aquatic ecology, and the salinization of salt lakes affects the DOM composition. To the best of our knowledge, no study has explored the effects of salinity on salt lake DOM composition at the molecular level. In this work, we selected Qinghai Lake (QHL) and Daihai Lake (DHL) as typical saline lakes. The two lakes have similar geographical and climatic conditions, and the salinity of QHL is higher than that of DHL. Fourier transform ion cyclotron resonance mass spectrometry coupled with electrospray ionization was applied to compare the DOM molecular composition in the two lakes. At higher salinity, the DOM showed larger average molecular weight, higher oxidation degree, and lower aromaticity. Moreover, the proportion of DOM that is vulnerable to microbial degradation (e.g., lipids), photo-degradation (e.g., aromatic structures), or both processes (e.g., carbohydrates and unsaturated hydrocarbons) reduced at higher salinity. On the contrary, compounds that are refractory to microbial degradation (e.g., lignins/CRAM-like structures and tannins) or photo-degradation (e.g., aliphatic compounds) accumulated. Our study provides a useful and unique method to study DOM molecular composition in salt lakes with different salinity and is helpful to understand DOM transformation during the salinization of salt lakes.